Pillaging plucking plundering ransacking proteomes via CPLL technology - Pier Giorgio Righetti; Egisto Boschetti (Open Journal of Proteomics and Genomics - Peertechz Publications, 2023)
No proteome can be considered "democratic", but rather "oligarchic" since a few proteins dominate the landscape and often obliterate the signal of the rare ones. That is the reason why most scientists lament that, in proteome analysis, the same set of abundant proteins is repeatedly seen. Current pre-fractionation techniques, one way or another, are besieged by problems, in that they are based on a "depletion principle", i.e. elimination of unwanted species. Yet "democracy" calls for giving "equal rights" to everyone. One way to achieve that would be the use of libraries of combinatorial ligands coupled to spherical beads. When these beads are contacted with complex proteomes (e.g., human urines and sera, egg white, any cell or tissue lysate) of widely differing protein composition and relative abundances, they are able to "normalize" the protein population, by sharply reducing the concentration of the most abundant components while simultaneously enhancing the level of the most dilute components. It is felt that this method could offer a strong step forward in bringing the "unseen proteome" (due to either low abundance and/or presence of interferences) within the detection capabilities of current proteomics detection methods. Examples are given of the normalization of human urine and sera samples, resulting in the discovery of a host of proteins previously unreported. These beads can also be used to remove host cell proteins from purified recombinant proteins or proteins purified from natural sources that are intended for human consumption. These proteins typically reach purities of the order of 98%: higher purities often become prohibitively expensive. Yet, if incubated with Combinatorial Peptide Ligand Libraries (CPLL), even these impurities can be effectively removed with minute losses of the main, valuable product.